Correlation between phenotypic characteristics and DNA relatedness within Enterococcus faecium strains. - Teixeira, L M (1995)
We noted that a number of enterococcal strains isolated from human clinical specimens resembled Enterococcus faecium but were able to produce acid from glycerol, raffinose, and/or sorbitol, while others failed to form acid from mannitol. An additional concern was that many of these strains with atypical phenotypic characteristics also appeared to acquire vancomycin resistance. In order to determine if such atypical strains were variants of E. faecium or new Enterococcus species, 35 E. faecium or E. faecium-like strains (grouped into 10 phenotypes on the basis of the results of the following tests: capacity to form acid from glycerol, mannitol, raffinose, or sorbitol and susceptibility to vancomycin) and four strains of Enterococcus faecalis were taken from our culture collection, analyzed for their whole-cell protein profiles by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and identified to the species level by DNA-DNA reassociation experiments. All E. faecium-like strains, including four mannitol-negative variants, conformed to at least two of three DNA-DNA relatedness criteria: they were 70% or more related to the type strain of E. faecium at optimal conditions, they had less than 5% divergence within the related sequences, and they had a relatedness of 60% or greater under stringent conditions. The protein profiles of atypical strains were similar to those of typical strains and were easily distinguishable from those of E. faecalis and other enterococcal species. The five E. faecalis strains were 12 to 16% related to the E. faecium type strain. These results indicate that the phenotypic description of E. faecium should include all of these variable characteristics.